HUBUNGAN D ISIPLIN KERJA DAN KEPUASAN KERJA DENGAN KINERJA PEGAWAI PADA DINAS PENDIDIKAN DAN KEBUDAYAAN PROVINSI BENGKULU - Heru Orbandi; Nia Indriasari; Ida Ida Anggriani (Universitas Muhammadiyah Bengkulu, 2021)
ABSTRACTTarget of in this research is to know relation discipline of work with performance employee at Department of Education and Culture Bengkulu Province and to know satisfaction of work with performance employee at Department of Education and Culture Bengkulu Province. Method Analysis the used is correlation of spearman hypothesis test and rank with test t. Analyse correlation of rank spearman to relation discipline of work with performance employee at Department of Education and Culture Bengkulu Province obtained by value 0,897 criterion very strong because result of its correlation lay in coefficient interval between 0,800 - 1,000. From result of relation hypothesis test between discipline of work with performance employee at Department of Education and Culture Bengkulu Province is 17,355 so that can be concluded that discipline of work have relation of significant with performance employee at Department of Education and Culture Bengkulu Province because value of t count bigger than t of is tables of (1,666). Correlation analysis of rank spearman to satisfaction of work with performance employee at Department of Education and Culture Bengkulu Province obtained by value 0,876 criterion very strong because result of its correlation lay in coefficient interval between 0,800 – 1,000. From result of relation hypothesis test between satisfaction of work with performance employee at Department of Education and Culture Bengkulu Province is 15,505 so that can be concluded that satisfaction of work (X2) have relation of significant with performance employee at Department of Education and Culture Bengkulu Province because value of t count bigger than t of t tables of (1,666).Keyword: Discipline of Work, satisfaction of Work, Performance